Suicide Ideation and Behavior as Risk Factors for Subsequent Suicide in Schizophrenia: A Nested Case–Control Study. Issue 4 (2nd August 2018) - Clapham, Eric; Bodén, Robert; Brandt, Lena; Jönsson, Erik G.; Bahmanyar, Shahram; Ekbom, Anders; Ösby, Urban; Reutfors, Johan
Abstract : Objective: To investigate suicide ideation and behavior as risk factors for suicide in schizophrenia during varying time periods. Method: Cases were 84 patients who died by suicide within 5 years from diagnosis in a source population of patients discharged for the first time from psychiatric hospitals in Stockholm County, Sweden, with a schizophrenia spectrum diagnosis. One control was individually matched with each suicide case. Data were retrieved from clinical records in a blind fashion. Thoughts of death, thoughts of suicide, suicide plan, and suicide attempt during varying time periods were investigated as risk factors for subsequent completed suicide. Results: In adjusted analyses, thoughts of suicide, suicide plan, and suicide attempt were significantly associated with subsequent completed suicide in the following year. The highest suicide risk was found within a year following suicide attempt (adjusted OR 9.9, 95% confidence interval 2.5–39.0). The association between suicide ideation and behavior and subsequent suicide declined over time. Conclusions: Several types of suicide ideation and behavior were associated with suicide, and the association was stronger for suicidal behavior. The clinical significance of suicidal communication appears highest during the following month or/and year. Many suicides occurred without recorded short‐term suicidal communication.